Composite metal foil and lithium battery comprising same
By using composite metal foils in lithium batteries, including metal layers such as nickel and free zinc or tin, the problems of copper foil corrosion and irregular deposition of lithium in sulfur-based solid electrolyte lithium batteries are solved, and the improvement of battery life and the reduction of reactivity are achieved.
Patent Information
- Application Number
- CN202411166133.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-05-22
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-15
AI Technical Summary
In lithium battery systems using sulfur-based solid electrolytes, existing copper foils are easily corroded by hydrogen sulfide, affecting battery life; at the same time, if the surface of the current collector is not lithium-friendly, it is easy to cause irregular deposition of lithium, resulting in lithium dendrites, forming short circuits.
A composite metal foil is used, including a conductive substrate, a first metal layer (nickel) and a second metal layer (free zinc, tin, indium, silver or alloys thereof), and the nucleation overpotential of the second metal layer is lower than that of the first metal layer, for electrodes of the lithium battery.
Through the use of composite metal foil, it can be used in lithium batteries containing sulfur-based solid electrolytes, maintain battery performance and improve battery life, and reduce reactivity with sulfide solid electrolytes.
Smart Images

Figure CN119833639A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lithium battery related technology, and in particular to a composite metal foil and a lithium battery containing the composite metal foil. Background Art
[0002] In lithium battery systems using sulfur-based solid electrolytes, because hydrogen sulfide (H2S) is generated, existing copper foil is not enough to resist H2S corrosion and will affect battery life. Therefore, there is currently research on using stainless steel to replace copper foil. Furthermore, if it is a sulfide solid-state battery with no negative electrode, low lithium or lithium metal negative electrode, the function of the collector in its structure is no longer just a simple current collection function. If the surface of the collector is not lithium-philic, lithium is easily deposited irregularly, causing the formation of lithium dendrites to form a short circuit. Therefore, it is necessary to develop new collector materials to overcome the above problems. Summary of the invention
[0003] The present invention is directed to a composite metal foil suitable for lithium batteries containing sulfur-based solid electrolytes.
[0004] The present invention is also directed to a lithium battery having improved battery life.
[0005] According to an embodiment of the present invention, a composite metal foil comprises a conductive substrate, a first metal layer and a second metal layer. The first metal layer is disposed on at least one surface of the conductive substrate and is in direct contact with the conductive substrate, and the first metal layer is nickel (Ni). The second metal layer is disposed on the surface of the first metal layer. The nucleation overpotential of the second metal layer is lower than the nucleation overpotential of the first metal layer, and the material of the second metal layer is at least one selected from the group consisting of zinc (Zn), tin (Sn), indium (In), silver (Ag), zinc alloy and tin alloy.
[0006] According to another embodiment of the present invention, a lithium battery includes a sulfur-based solid electrolyte, and an electrode of the lithium battery includes the composite metal foil described above.
[0007] Based on the above, the composite structure formed by the specific metal on the surface of the conductive substrate of the present invention can be applied to lithium batteries containing sulfur-based solid electrolytes, and can maintain battery performance and improve battery life. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1A is a schematic cross-sectional view of a composite metal foil according to an embodiment of the present invention;
[0009] Figure 1B is a schematic cross-sectional view of a composite metal foil according to another embodiment of the present invention;
[0010] Figure 2 is a schematic cross-sectional view of a composite metal foil according to another embodiment of the present invention;
[0011] Figure 3 is a schematic diagram of a CV curve of a lithium battery containing the composite metal foil of Example 1;
[0012] Figure 4 is a schematic diagram of a CV curve of a lithium battery containing the composite metal foil of Comparative Example 5;
[0013] Figure 5 is a schematic diagram of a CV curve of a lithium battery containing the composite metal foil of Example 6;
[0014] Figure 6 is a schematic diagram of a CV curve of a lithium battery containing the composite metal foil of Example 8;
[0015] Figure 7 This is a schematic diagram of the CV curve of a lithium battery containing the composite metal foil of Comparative Example 11. DETAILED DESCRIPTION
[0016] Reference will now be made in detail to exemplary embodiments of the present invention, examples of which are illustrated in the accompanying drawings. Whenever possible, the same reference numerals are used in the drawings and the description to refer to the same or like parts.
[0017] Figure 1A is a schematic cross-sectional view of a composite metal foil according to an embodiment of the present invention.
[0018] Please refer to Figure 1A The composite metal foil includes a conductive substrate 100, a first metal layer M1 and a second metal layer M2. The first metal layer M1 is disposed on two surfaces 100a and 100b of the conductive substrate 100 and is in direct contact with the conductive substrate 100. However, the present invention is not limited thereto. In another embodiment, the first metal layer M1 may be disposed only on one surface 100a of the conductive substrate 100, such as Figure 1BAs shown. The first metal layer M1 is nickel (Ni), and the thickness t1 of the first metal layer M1 is, for example, 0.05 μm to 2 μm, or 0.15 μm to 2 μm, or 0.2 μm to 2 μm. The conductive substrate 100 is copper foil or polymer composite copper foil, wherein if the conductive substrate 100 is copper foil, the thickness is about 3 μm to 30 μm, but is not limited thereto. As for the polymer composite copper foil, it can be a sandwich structure composite foil, for example, including a polymer film and a copper metal layer arranged on both sides thereof, wherein the copper metal layer has a thickness of about 0.5μm to 5μm, and the polymer film can be a high temperature resistant polymer, such as polyethylene terephthalate (PET), polyimide (PI), polyester (PE), polypropylene (PP), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polydimethylsiloxane (PDMS) or a combination of the foregoing, and its thickness can be about 1μm to 10μm.
[0019] The second metal layer M2 is disposed on the surface S1 of the first metal layer M1, and the surface S1 here refers to the outer surface of the first metal layer M1. The nucleation overpotential of the second metal layer M2 is lower than the nucleation overpotential of the first metal layer M1. The material of the first metal layer M1 can be nickel, and the material of the second metal layer M2 can be selected from at least one of the group consisting of zinc (Zn), tin (Sn), indium (In), silver (Ag), zinc alloy and tin alloy. "Nucleation overpotential" refers to the difference between the lowest point of the polarization overpotential generated by lithium deposition on the copper foil and the equilibrium potential. In one embodiment, the above-mentioned zinc alloy includes a zinc-nickel alloy, and the zinc content in the zinc-nickel alloy can be above 80wt%, such as above 90% or above 95%. In one embodiment, the above-mentioned tin alloy includes a tin-nickel alloy, and the tin content in the tin-nickel alloy is above 80wt%, such as above 90% or above 95%. In this embodiment, the thickness t2 of the second metal layer M2 is 0.01 μm to 0.2 μm, or 0.03 μm to 0.2 μm.
[0020] Figure 2 It is a schematic cross-sectional view of a composite metal foil according to another embodiment of the present invention, wherein the same element symbols as those in the previous embodiment are used to represent the same or similar film layers or parts, and the same film layers or parts are not described in detail.
[0021] exist Figure 2In the embodiment, the composite metal foil may further include an anti-oxidation layer 200, which may cover the surface S2 of the second metal layer M2, and the surface S2 here refers to the outer surface of the second metal layer M2. In one embodiment, the anti-oxidation layer 200 may be formed by chromic acid, benzotriazole (BTA), carboxybenzotriazole (CBTA) or methylbenzotriazole (MBTA).
[0022] Figure 2 The manufacturing method of the composite metal foil is, for example but not limited to, firstly electroplating the surfaces 100a and 100b of the conductive substrate 100 to form a first metal layer M1, then electroplating the second metal layer M2 on the surface S1 of the first metal layer M1, and then using a dipping method or a coating method to form an anti-oxidation layer 200 on the surface S2 of the second metal layer M2. In addition, after the anti-oxidation layer 200 is formed, heat treatment can be selectively performed in an environment of 100°C to 250°C for 1 to 60 minutes to enhance the structural density of the composite metal foil.
[0023] Several experiments are listed below to verify the efficacy of the present invention, but these experiments and their results are not intended to limit the scope of application of the present invention.
[0024] <Preparation Example>
[0025] Step 1. Prepare copper plating solution (Cu 2+ :60g / L (CuSO4), H2SO4:90g / L, Cl-:30ppm (HCl, DP-111L additive from Tianhong Company) and heated it to 40°C, the speed of the rotating column electrode was controlled at 800rpm, and the current density was 50A / dm 2 Electroplating was performed for 48 seconds to obtain 8 μm of bottom copper (ie, conductive substrate).
[0026] Step 2: Perform the first metal layer electroplating to form the first metal layer on the surface of the copper foil. The method is to place the rotating column electrode containing the bottom copper into the plating solution and place it at a temperature of 50°C and a current density of 5A / dm 2 The electroplating time is controlled (eg, from several seconds to tens of seconds) to obtain a first metal layer of a predetermined thickness. The composition of the plating solution is shown in Table 1 below, and the material and thickness of the first metal layer are shown in Table 2 below.
[0027] Step 3: Electroplating the second metal layer to form the second metal layer on the first metal layer of the copper foil. The method is to place the rotating column electrode containing the base copper and the first metal layer into the plating solution and electroplate the second metal layer at a current density of 1A / dm 2The electroplating time is controlled (eg, a few seconds) to obtain a second metal layer of a predetermined thickness. The composition of the plating solution is shown in Table 1 below, and the material and thickness of the second metal layer are shown in Table 2 below.
[0028] Table 1
[0029]
[0030] Step 4. After washing the electroplated product of step 3, immerse it in an anti-oxidation layer (chromic acid) solution to form an anti-oxidation layer.
[0031] Optional step 5. Place the finished product of step 4 in an atmosphere furnace for heat treatment at a temperature as shown in Table 2 for a time of less than 30 minutes.
[0032] Table 2 (Except for Comparative Example 2, all conductive substrates are 8 μm bottom copper (HTCu))
[0033]
[0034] 〈Ingredient Analysis〉
[0035] The composite metal foils of Example 1, Example 12, Comparative Example 5 and Comparative Example 12 were subjected to component analysis by completely dissolving the metal foils in concentrated hydrochloric acid and then diluting them for ICP component testing. The analysis results are shown in Table 3.
[0036] Table 3
[0037]
[0038] Because the sample is dissolved during component analysis, the Ni / SnNi result (such as Example 12) will have a much higher Ni content. If we only look at the sample with only the tin-nickel alloy layer (Comparative Example 12), the weight ratio of Sn to Ni is about 0.975:0.025. Similarly, if we only look at the sample with only the zinc-nickel alloy layer (Comparative Example 5), the weight ratio of Zn to Ni is about 0.967:0.033.
[0039] 〈Battery Characteristics Analysis〉
[0040] The solid electrolyte is a sulfide solid electrolyte of argyrodite type (Li6PS5Cl). The composite metal foils of Examples 1 to 12 and Comparative Examples 1 to 13 in Table 2 are used as working electrodes and lithium metal foil is used as a counter electrode to assemble into a CR2032-type button cell (all-solid-state half-cell).
[0041] Cyclic voltammetry (CV) was performed at room temperature (25°C) with a scan rate (Scan rate) of 5mV / s, from the open-circuit potential to a low potential of 0.01V (vs.Li / Li+), and then to a high potential of 5V (vs.Li / Li+), for 100 cycles.
[0042] During the cyclic voltammetry test, the current density generated by scanning from high potential to low potential is called reduction current density; the current density generated by scanning from low potential to high potential is called oxidation current density. If the absolute value of oxidation current density or reduction current density is lower, it means that the reactivity between the working electrode and the sulfide solid electrolyte is lower, which can be used to judge the sulfurization resistance of the composite metal foil. The test results are shown in Tables 4 and 5.
[0043] Table 4
[0044]
[0045] From Table 4, it can be seen that Comparative Example 1 is a pure copper foil, and its CV results have an absolute value of redox current density greater than 30 μA cm above the 10th cycle. -2 , which means that the pure copper foil has high reactivity with the sulfide solid electrolyte; Comparative Example 2 is commercially available stainless steel, which has a small absolute value of redox current density but high cost. Comparative Examples 3 and 4 add a nickel layer on the copper foil, but the absolute value of the redox current density is greater than 30μA cm in the 10th to 20th cycles. -2 As for Examples 1 to 3, in addition to the nickel layer, a zinc layer is added to the copper foil. The CV results show that the absolute values of the redox current density after 100 cycles are all less than 30 μA cm -2 However, when zinc-nickel co-plating was used on the copper foil (Comparative Examples 5-6), the CV results showed that the absolute value of the redox current density was greater than 30 μA cm after 20 cycles. -2 Similarly, the CV results of direct tin plating on copper foil (Comparative Examples 7 to 9) show that the absolute value of the redox current density is greater than 30 μA cm after 10 cycles regardless of whether heat treatment is performed or not. -2 .
[0046] Also, please refer to Figure 3 and Figure 4 ,in Figure 3 is the CV curve of the lithium battery containing the composite metal foil of Example 1, Figure 4 It is the CV curve of the lithium battery containing the composite metal foil of Comparative Example 5. Figure 3 The curve of whether it is the 1st or 100th cycle, the change of current density is obviously smaller than Figure 4, which means that the composite metal foil of the present invention has low reactivity with the sulfide solid electrolyte.
[0047] Table 5
[0048]
[0049] From Table 5, it can be seen that in Examples 5 to 8, a nickel layer and a tin-nickel layer are plated on the copper foil. The CV results show that the absolute value of the oxidation current density is less than 30 μA cm regardless of whether the heat treatment is performed or not. -2 The absolute value of the reduction current density after 100 cycles is less than 30 μA cm -2 In Comparative Examples 10 to 12, where the Sn-Ni layer is directly plated on the copper foil, the CV results show that the absolute value of the redox current density is greater than 30 μA cm after 10 cycles, regardless of whether the heat treatment is performed or not. -2 Examples 9 to 12 are copper foils with 200 nm nickel layers and tin-nickel layers of different thicknesses. The CV results show that the absolute values of the redox current density of the heat-treated samples are lower and are all less than 30 μA cm -2 In Comparative Example 13, in which the copper foil is first plated with zinc and then nickel, the CV result shows that the absolute value of the redox current density is greater than 30 μA cm after the 10th cycle. -2 .
[0050] Also, please refer to Figures 5 to 7 ,in Figure 5 is the CV curve of the lithium battery containing the composite metal foil of Example 6, Figure 6 is the CV curve of the lithium battery containing the composite metal foil of Example 8, Figure 7 This is the CV curve of the lithium battery containing the composite metal foil of Comparative Example 11. Figure 5 and Figure 6 The change in current density is significantly smaller than Figure 7 , which means that the composite metal foil containing a double metal layer of the present invention has a lower reactivity with the sulfide solid electrolyte than the composite metal foil with only a single tin-nickel layer, regardless of whether it has been heat treated or not.
[0051] 〈High-temperature battery characteristics〉
[0052] CR2032-type button cells containing the composite metal foils of Comparative Example 1, Comparative Example 2 and Example 1 were prepared in the manner described in the battery characteristics analysis. Cyclic voltammetry was performed at 55°C, with a scan rate of 5 mV / s, from the open circuit voltage to a low potential of 0.01 V (vs. Li / Li+), and then to a high potential of 5 V (vs. Li / Li+), for 10 cycles. The test results are shown in Table 6.
[0053] Table 6
[0054]
[0055] It can be seen from Table 6 that the composite metal foil of the present invention (Example 1) is more stable at high temperatures than the stainless steel foil (Comparative Example 2).
[0056] 〈Nucleation Overpotential〉
[0057] Test method: A CR2032-type button cell containing the composite metal foil in Table 7 below was prepared according to the method described in the battery characteristics analysis, and the charge and discharge current density was set to 0.01 to 0.05 mA / cm 2 , the charging time is 0.8 hours.
[0058] Nucleation overpotential (ΔV nu ) is defined as the difference between the lowest point of polarization overpotential generated by lithium deposition on copper foil and the equilibrium potential, as shown in formula (1):
[0059] ΔV nu = V nu -V balance (1)
[0060] In formula (1), V nu is the lowest potential after lithium metal deposition (V); V balance is the equilibrium stable potential (V).
[0061] ΔV obtained by measuring the potential and calculating nu It is recorded in Table 7 below.
[0062] Table 7
[0063] <![CDATA[ΔV nu (mV)]]> Comparative Example 1 (8μm base copper) 47.3 Comparative Example 2 (Stainless Steel Foil) 47.3 Comparative Example 4 (Copper Foil / 200nm Ni) 44 Comparative Example 5 (Copper Foil / 180nm ZnNi) 43.8 Example 1 (Copper foil / 200nm Ni / 30nm Zn) 13.5 Example 10 (Copper foil / 200nm Ni / 45nm SnNi) 20.5 Example 11 (Copper foil / 200nm Ni / 30nm SnNi, heat treatment) 6 Example 12 (Copper foil / 200nm Ni / 45nm SnNi, heat treatment) 7.9
[0064] It can be seen from Table 7 that the nucleation overpotential of the composite metal foil of the present invention is lower than that of forming only a nickel layer on a copper foil, that is, less than 44 mV, for example, less than 30 mV or less than 20 mV.
[0065] Based on the above experimental results, a simple evaluation was performed according to the following numerical range to obtain the following Table 8.
[0066] Reactivity at room temperature:
[0067] X: Maximum redox current density (absolute value) of the 100th cycle > 30 μA / cm 2 .
[0068] O: Maximum redox current density (absolute value) of the 100th cycle <30μA / cm 2 .
[0069] Reactivity at high temperature:
[0070] X: Maximum redox current density (absolute value) of the 10th cycle > 30 μA / cm 2 .
[0071] O: Maximum redox current density (absolute value) of the 10th cycle <30μA / cm 2 .
[0072] Nucleation overpotential:
[0073] X:>30mV.
[0074] O: <30mV.
[0075] Table 8
[0076]
[0077] It can be seen from Table 8 that the composite metal foil of the present invention has low reactivity to sulfide solid electrolytes and has a small nucleation overpotential, so it is suitable for lithium batteries containing sulfur-based solid electrolytes, thereby improving battery performance and battery life.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite metal foil, characterized in that: include: Conductive substrate; A first metal layer is disposed on at least one surface of the conductive substrate and is in direct contact with the conductive substrate; as well as The second metal layer is disposed on the surface of the first metal layer, wherein The first metal layer is nickel, The nucleation overpotential of the second metal layer is lower than that of the first metal layer, and a material of the second metal layer is at least one selected from the group consisting of zinc, tin, indium, silver, zinc alloy and tin alloy.
2. The composite metal foil according to claim 1, characterized in that: The zinc alloy includes a zinc-nickel alloy, and the zinc content in the zinc-nickel alloy is above 80wt%.
3. The composite metal foil according to claim 1, characterized in that: The tin alloy includes a tin-nickel alloy, and the tin content in the tin-nickel alloy is above 80 wt %.
4. The composite metal foil according to claim 1, characterized in that: The thickness of the first metal layer is 0.05 μm to 2 μm.
5. The composite metal foil according to claim 1, characterized in that: The thickness of the second metal layer is 0.01 μm to 0.2 μm.
6. The composite metal foil according to claim 1, characterized in that: It also includes an anti-oxidation layer covering the surface of the second metal layer.
7. The composite metal foil according to claim 6, characterized in that: The anti-oxidation layer is formed by chromic acid, benzotriazole, carboxylbenzotriazole or methylbenzotriazole.
8. The composite metal foil according to claim 1, characterized in that: The conductive substrate includes copper foil or polymer composite copper foil.
9. The composite metal foil according to claim 8, characterized in that: The polymer composite copper foil comprises: polymer films; and The copper metal layer is arranged on both sides of the polymer film.
10. The composite metal foil according to claim 9, characterized in that: The polymer film includes polyethylene terephthalate, polyimide, polyester, polypropylene, polyacrylonitrile, polymethyl methacrylate, polydimethylsiloxane or a combination thereof.
11. A lithium battery, characterized in that: Contains a sulfur-based solid electrolyte, and the electrode of the lithium battery comprises the composite metal foil according to any one of claims 1 to 10.
Citation Information
Cited By
Composite conductive agent, preparation method thereof and solid-state battery
CN121035208A